Serum Levels of Brain-Derived Neurotrophic Factor and Other Neurotrophins in Elite Athletes: Potential Markers of the Use of Transcranial Direct Current Stimulation in Sport - Donati, Francesco; Sian, Veronica; Biasini, Giorgia Morgan; de la Torre, Xavier; Folchitto, Fabrizia; Botrè, Francesco (Frontiers in Sports and Active Living, 2021)
Transcranial Direct Current Stimulation (tDCS) is a non-invasive brain stimulation that may enhance mental and physical performance in sports, representing a potential new form of doping (“brain doping” or “electromagnetic doping”). This study aims to identify diagnostic biomarkers for detecting the possible abuse of tDCS in sport. Brain-Derived Neurotrophic Factor (BDNF) and other neurotrophins (NT, such as beta nerve growth factor, NGF) were pre-selected as potential candidates since their serum values have been observed to change following tDCS. Neurotrophins were measured using ELISA assays in 92 serum samples collected from elite athletes, classified by sex (males = 74; females = 18), age (range 17–25 n = 27, 26–35 n = 36, and over 35 n = 14; age not known n = 15), type of sports practiced (endurance n = 74; power n = 18), and type of sample collection (“in competition” n = 24; “out of competition” n = 68). Single nucleotide polymorphisms (rs6265, rs11030099, and rs11030100) were genotyped on 88 samples to determine their influence on the analytes' basal levels. Athletes older than 35 presented higher BDNF values than younger individuals (p < 0.05). Samples collected “in competition” showed higher BDNF concentrations than those collected “out of competition” (p < 0.05). The studied polymorphisms appeared to affect only on proBDNF, not altering BDNF serum concentrations. NT-3 and NT-4 were poorly detectable in serum. Our results suggest that BDNF can be considered as a first biomarker to detect the abuse of tDCS in sport doping. Further studies are necessary to assess whether proBDNF and beta NGF can also be considered suitable biomarkers to detect the recourse to electromagnetic brain stimulation in sports, especially in the case their serum levels can be monitored longitudinally. To the best of our knowledge, this is the first study aimed to pre-select serum biomarkers to identify the use of tDCS, and represents the first step toward the development of an indirect strategy, preferably based on the longitudinal monitoring of individual data, for the future detection of “brain doping” in sports.